Through the Inner World: Development of Reclusion Tendency Scale - Yıldırım, B.K.; Ekşi, H.; Kardaş, S.; Ekşi, F. (Halil Eksi, 2023)
The aim of this study is to develop a valid and reliable scale to determine the reclusion tendency levels in adults. The sample group is consistent with adults between the ages of 18-60 (Mage=26.2 years; age range: 18-33 years). A literature review was performed and existing scales were examined prior to this study. Potential items were formed. Then the data collection using the template scale began. The collected data was used for exploratory and confirmatory factor analysis and for the purpose of testing the structural validity of the scale. As a result of the exploratory factor analysis, a measuring tool of 22 items consisting of four sub-dimensions of internal observation, spirituality, productivity, and autonomy sub-dimensions that explain the 58,51% of the total variations was formed. There is a meaningful positive correlation identified between the Reclusion Tendency Scale and the Preference For Solitude scale (r=.49; p<.001). The total reliability coefficient is calculated .92; .88 for “internal observation”, .88 for “spirituality”, .66 for “autonomy”, and .75 for “productivity” sub-dimensions. The findings from this study suggest that the reclusion tendency scale is a valid and reliable scale when tested in a sample of young adults. ©Copyright 2023 by Author(s).
Keywords: Autonomy; Internal Observation; Productivity; Reclusion; Scale Development; Spirituality